Transient epileptic amnesia. - Zeman, A; Butler, C (2010)
PURPOSE OF REVIEW: Case reports over the past 100 years have raised the possibility that epilepsy can manifest itself in episodes of amnesia. Recent research has established that this is indeed the case, and indicates that characteristic varieties of interictal memory disturbance co-occur with this form of epilepsy. RECENT FINDINGS: Transient epileptic amnesia is a distinctive syndrome of temporal lobe epilepsy principally affecting middle-aged people, giving rise to recurrent, brief attacks of amnesia, often occurring on waking. It is associated with novel forms of interictal memory disturbance: accelerated long-term forgetting, remote memory impairment, especially affecting autobiographical memory, and topographical memory impairment. The seizure focus lies in the medial temporal lobes. The seizures respond promptly to treatment, whereas the interictal impairments generally persist. Further work is required to establish whether the interictal memory impairment is due to physiological or structural disturbance. SUMMARY: Transient epileptic amnesia is an under-recognized but treatable cause of transient memory impairment. Accelerated long-term forgetting and autobiographical amnesia, which are invisible to standard memory tests, help to explain the discrepancy between normal test performance and prominent memory complaints among patients with epilepsy. Further investigation of these forms of memory impairment promises to shed light on processes of human memory.